Histological structure of rat preantral follicles after vitrification using date juice as a natural extracellular cryoprotectant - Nova Anita; Aisyah Safrina; Ahmad Aulia Jusuf; Rahimi Syaidah (Universitas Airlangga, 2026)
Cold shock, cryoinjury, and apoptosis remain major challenges in ovarian vitrification because they compromise the structural integrity of follicular cells. Date juice (DJ), which contains natural sugars and antioxidant compounds, may provide cryoprotective effects during vitrification. This study evaluated the effectiveness of DJ combined with ethylene glycol (EG) in preserving the structural integrity of preantral follicles. Ovaries were collected from 24 female Sprague–Dawley rats and assigned to eight groups: CN and CV (0.9% NaCl), CT1 (7.5% EG), CT2 (15% EG), T1 (7.5% EG + 7.5% DJ), T2 (7.5% EG + 15% DJ), T3 (15% EG + 7.5% DJ), and T4 (15% EG + 15% DJ). After vitrification, ovarian sections were stained with hematoxylin and eosin (H&E). Follicular integrity was evaluated histologically as the percentages of intact and non-intact primordial, primary, and secondary follicles. Statistical analysis (P ≤ 0.05) showed significant differences between the non-vitrified and vitrified control groups across all follicle stages. T1 yielded the highest percentage of intact primordial follicles (95.851%) and the lowest percentage of non-intact primordial follicles (4.149%). T2 produced the best outcomes for primary and secondary follicles, with intact follicle percentages of 90.343% and 87.158%, respectively. Overall, combining EG (7.5% or 15%) with 7.5% DJ improved follicular integrity compared with EG alone. These findings suggest that DJ has potential as a natural extracellular cryoprotectant for ovarian tissue vitrification.